Aluminium tolerance in bean traditional cultivars from Madeira - Domingues, Ana Maria (2019)
Common bean (Phaseolus vulgaris L.) is the most important legume crop in the world, providing low-cost, high quality protein, minerals and dietary fiber for human nutrition. The crop was originated from diversity centers in America and exhibits adaptation abilities to different environmental conditions, including soil with low pH. Acid soils occupy 30% of the agro ecosystem areas in the world. In Madeira, acid Andosols and unsatured Cambisols are the dominant groups of soils. Generally, under acidic and infertile conditions, besides of H+ toxicity, soluble aluminium (Al) is the most important abiotic factor limiting plant development and crop productivity. In the field, the hidden roots are also affected and the reduction of root growth under Al stress can be clearly observed in early stages. Seedlings of fifty bean accessions from the Archipelago of Madeira were tested under controlled conditions in the presence of 50 µM Al at pH 4.4. In general, the tested germplasm appeared to be sensitive or very sensitive to Al toxicity. However, fifteen traditional cultivars clearly exhibited elevated Al-tolerance, with an average root relative elongation (RRE) exceeding 50%, while top six accessions surpassed the 60% RRE mark. The Madeira bean germplasm is a valuable resource for sustainable crop production in acid soils and it could be used as parental lines in breeding programs aimed for Al tolerance in common beans.